A New Group Decision-making Method Based on Fuzzy Set Operations (European Journal of Pure and Applied Mathematics, 2011)
In this study we suggest a new group decision-making method which isbased on some basic fuzzy set operations. By using this method, wecan get two types of results. First, we can identify whichalternative is the best. The second result, a crucial point of thiswork, is the screening of decision-makers. The decision-makersshould be serious and responsible in giving their opinions otherwisethe process will eliminate them because of their inappropriateevaluations to the alternatives compared with that of the otherdecision-makers. We also discuss an application to demonstrate theprocess of the method.